Assessment water productivity of barley varieties under water stress by AquaCrop model - Farid Hellal; Hani Mansour; Mohamed Abdel-Hady; Saied El-Sayed; Chedly Abdelly (AIMS Agriculture and Food, 2019)
Drought is the major a biotic stress that reduces plant growth and crop productivity worldwide. AquaCrop model is one of the most widely used simulation models, which simulates the growth, yield and water productivity of the crops. Field experiment was carried out in the Experimental Research Station of Nubaria, during two seasons of 2016/2017 and 2017/2018. The study to assess water productivity of Mediterranean barley (Egyptian, Tunisian, Algerian and Morocco) varieties grown under water stress condition (40% of water holding capacity) compared to normal one (75% of water holding capacity) by AquaCrop model. Deviations (%) between observed under normal irrigation water and observed water deficit (stress), AquaCrop model normal and AquaCrop model stress, data obtained were (2.36, 1.84, 2.25 and 1.59%) for Egyptian barley varieties, respectively. For Tunisian barley varieties, deviations (%) were (2.06, 1.59, 2.78 and 3.62%), respectively. For Algerian barley varieties, were (2.12, 1.66, 2.88 and 3.71%), respectively. The percentage of absolute difference between the percentage of variation in the case of water stress and the case without water stress treatment was 5.36% under Egyptian varieties, followed by Morocco varieties (12.78%). Egyptian varieties are the least tolerant of water stress treatment where the percentage difference in the absolute difference between the cases is equal to 25%.